Protecting the world's finest athletes: periodic health evaluation practices of the top performing National Olympic Committees from the 2016 Rio or 2018 PyeongChang Olympic Games - Nabhan, D.; Taylor, D.; Lewis, M.; Bahr, R. (British Journal of Sports Medicine, 2021)
AIM: To describe the periodic health evaluation (PHE) practices of the top performing National Olympic Committees (NOCs).